Choice in a World of New School Types. (11th August 2013) - Butler, J. S.; Carr, Douglas A.; Toma, Eugenia F.; Zimmer, Ron
Abstract: As school choice options have evolved over recent years, it is important to understand what family and school factors are associated with the enrollment decisions families make. Use of restricted‐access data from the Early Childhood Longitudinal Study allowed us to identify household location from a nationally representative sample of students and to match households to the actual schools attended and other nearby schools. This matching is significant as previous research generally has not been able to link individual households to school enrollment decisions. Using these data, we examined the role that socioeconomic status, race, and ethnicity play in school enrollment decisions. One of our more interesting results suggests that the newest public alternative, charter schools, attracts families with higher socioeconomic status than those that traditional public schools attract. The attraction of charter schools, however, unlike traditional public schools, appears to be racially and ethnically neutral. Families do not choose a charter school because of its racial or ethnic composition, nor do race and ethnicity within a household influence its choice of charter schools. Other socioeconomic factors influencing charter school choice are more similar to factors explaining private school choice than to those factors explaining the choice of traditional public schools. The findings suggest that policies governing the design of charter schools should focus on broader socioeconomic diversity rather than race only.